2016
DOI: 10.1007/s13762-015-0927-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of key components of S. triqueter root exudates on fractions and bioavailability of pyrene–lead co-contaminated soils

Abstract: The key components of S. triqueter root exudates involved 4-oxo-pentanoic acid, succinic acid, glutaric acid, phthalate acid, citric acid, vanillic acid, myristic acid, pentadecanoic acid, decanoic acid, 14-methyl-pentadecanoic acid, hexadecanoic acid, octadecanoic acid and oleic acid, and the content of the water-soluble organic acids (citric acid, succinic acid and glutaric acid) significantly increased in pyrene and lead co-contaminated rhizosphere soil. These three water-soluble organic acids including cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 36 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…These changes are induced by root exudates that change the nutrients and metal supplies. Root exudates are released by root cells in the soil, including low molecular weight compounds (amino acids, organic acids, sugars, phenolic compounds) and compounds of high molecular weight (polysaccharides and proteins) [36,37]. Medas et al [38] reported that root exudates facilitate Zn silicate uptake in Euphorbia pithyusa L. In Arabidopsis halleri, Tsednee et al [39] observed that roots release nicotianamine (NA), a main chelator, which has a beneficial effect on improving Zn's solubilization and thus Zn accumulation.…”
Section: Sources and Bioavailability Of Zincmentioning
confidence: 99%
“…These changes are induced by root exudates that change the nutrients and metal supplies. Root exudates are released by root cells in the soil, including low molecular weight compounds (amino acids, organic acids, sugars, phenolic compounds) and compounds of high molecular weight (polysaccharides and proteins) [36,37]. Medas et al [38] reported that root exudates facilitate Zn silicate uptake in Euphorbia pithyusa L. In Arabidopsis halleri, Tsednee et al [39] observed that roots release nicotianamine (NA), a main chelator, which has a beneficial effect on improving Zn's solubilization and thus Zn accumulation.…”
Section: Sources and Bioavailability Of Zincmentioning
confidence: 99%